Investigation of a Cherenkov-based gamma-ray diagnostic for measurement of 17 MeV gamma-rays from T(D, γ)5He in magnetic confinement fusion plasmas. (1st February 2022) - Putignano, O.; Croci, G.; Muraro, A.; Cancelli, S.; Giacomelli, L.; Gorini, G.; Grosso, G.; Kushoro, M.H.; Marcer, G.; Nocente, M.; Rebai, M.; Tardocchi, M.
Abstract: At present, the only method for assessing the fusion power throughput of a reactor relies on the absolute measurement of 14 MeV neutrons produced in the D-T nuclear reaction. For ITER and DEMO, however, at least another independent measurement of the fusion power is required. The 5 He * nucleus produced in the D-T fusion reaction has two de-excitation channels. The most likely is its disintegration in an alpha particle and a neutron, D + T → 5 He * → α + n, by means of the nuclear force. There is however also an electromagnetic channel, with a branching ratio ∼10 −5, which leads to the emission of a 17 MeV gamma-ray, i.e. D + T → 5 He * → 5 He + γ . The detection of this gamma-ray emission could serve as an independent method to determine the fusion power. In order to enable 17 MeV gamma-ray measurements, there is need for a detector with some coarse energy discrimination and, most importantly, capable of working in a neutron-rich environment. Conventional inorganic scintillators, such as LaBr3 (Ce), have comparable efficiencies to neutrons and gamma-rays and they cannot be used for 17 MeV gamma-ray measurements without significant neutron shielding. In order to overcome this limitation, we here propose the conceptual design of a gamma-ray counter with a variable energy threshold based on the Cherenkov effect and designed to operate in intense neutron fields. The detector geometry has been optimized using Geant4 so to achieve a gamma-ray to neutron efficiency ratio better than 10 5 . The design is based on a gas Cherenkov detector and the photo-sensor is still to investigated.